SOME ISSUES OF THE FORMATION OF A COMPETITIVE TERRITORIAL ECONOMY IN THE CONTEXT OF INTEGRATION - Abdumuradovich, Sattorov Sanzhar (Scholar Express Journals, 2021)
The article analyzes the need for the formation of a competitive regional economy in the context of integration and its features. The article also analyzes the classification of theories of factors and models of the regional economy.
Keywords: regional policy; socio-economic development; key issues of economic development; statistical values